Implementation of Pancasila Values in Shaping National Morals Which Are Eroded by the Impact of Globalization - Riani Eva Syahfitri (International Journal of Students Education, 2024)
This research aims first to find out to what extent the values of Pancasila and national morals have been eroded as a result of globalization. Then secondly, to find out why this problem arises, namely that Pancasila and moral values in the younger generation are not well embedded in everyday life in the era of globalization. The research method used in this article is a Systematic Literature Review, the author searches for published articles related to the title or research topic that the researcher has determined, the articles searched are limited to 20 articles, then the researcher filters them to 12 articles that are deemed appropriate and close to each other. to answer this research. The research results show that from these articles it can be seen that the role of Pancasila and moral values in society among individuals has experienced a very large decline in this era of globalization. So that in this era of rapid globalization, the values of Pancasila and national morals must be revived again. The findings in this research are that there are still not many articles that write about Pancasila values in shaping the nation's morals in the world of education or in the era of globalization. So the researcher provides recommendations for the need for support from the government, educational institutions, students' environment and parents to work together to increase awareness among students and young people in awakening and instilling Pancasila values and national morals while also aiming to shape morals. from every young generation in the era of globalization.